Perancangan dan Pembuatan Sistem Monitoring Aktifitas Karyawan Berbasis WEB pada PT. HRL INTERNASIONAL - Rahmawati, Titasari; Sena, I Gede Wiarta; Albert, Nicholas Manuel (J-INTECH (Journal of Information and Technology), 2022)
In a company, monitoring employee activities is one of the most important processes to ensure the continuity of the desired business process. The problem faced at this time is that there is no monitoring process that is properly systemized because the employee monitoring process is done manually. Based on the problems above, this study aims to create a web-based employee activity monitoring system at PT. HRL International. The method used is System Development Life Cycle (SDLC) Waterfall and in the model design process data flow diagrams will be used. Based on the results of the black box testing of the functional system, the results are by the planned design, so this system can help solve problems that exist in PT. HTL INTERNASIONAL.